Inhabiting the Profile: Zach Blas’ Facial Weaponization Suite - Althoff, Sebastian (Intermédialités / Intermediality, 2018)
This article places Zach Blas’ Facial Weaponization Suite (2011–2014) in relation to the notion of algorithmic governmentality in order to reveal a tactic of disidentification. Algorithmic governmentality refers to the implementation of big data surveillance that does not render individuals visible, but rather circumvents them, thereby complicating the possibility of a critical engagement. Such critical engagement, however, can be envisioned through the Facial Weaponization Suite.